Local plastic deformation in the vicinity of topologically close-packed phases in a Ni-based single crystal superalloy - Sangwon Lee; Jeonghyeon Do; Baig Gyu Choi; Ujjval Bansal; Christoph Kirchlechner; Pyuck-Pa Choi; Subin Lee (Materials & Design)
The role of a topologically close-packed (TCP) phase (μ phase) on the plastic deformation of a Ni-based superalloy was investigated employing a combination of in situ scanning electron microscope micropillar compression and atomic-scale characterization using atom probe tomography and transmission electron microscopy. Micropillar tests revealed two distinct slip behaviors: TCP-free pillars deformed via multiple slip systems, whereas TCP-containing pillars deformed by single slip. Notably, while previous studies have reported fracture at the TCP/γ' interface, our findings revealed that in the TCP-containing pillars, deformation was rarely observed at the interface. Instead, slip predominantly occurred in regions approximately 50–100 nm away from the interface. Chemical analysis near the TCP/γ' interface via APT showed an excess Ta content near the interface increasing the antiphase boundary energy and enhancing local order strengthening. Moreover, an approximate 8% lattice misfit at the TCP/γ' interface, coupled with the elastic mismatch between the two phases, provided additional slip resistance in the vicinity of the interface. This study sheds light on the intricate interplay between TCP phase formation, microstructural evolution, and mechanical properties in Ni-based superalloys offering valuable insights into the role of the TCP phases.